PENGEMBANGAN BUKU AJAR MATAKULIAH BIOLOGI SEL BERBASIS IN SILICO - Dianing Eka Pupitasari; Mohamad Amin; Betty Lukiati (Graduate School of Universitas Negeri Malang, 2016)
The material presented in Cell Biology course one of them is the Cell Aging (Aging). In these materials can be developed research in Silico to broaden the knowledge of students with innovative bioinformatics approach based learning with a reverse screening method. The method used is Dick and Carey (2009) Model Development. The results of research in the form textbook Cell Biology courses based in Silico which has been validated by subject matter experts, media, and small-scale trials. Results from subject matter experts by 91.43% for feasibility component contents, 77.33% for eligibility presentation and 72.72% for the use of language. For media experts obtained 89.70% and 93% for small-scale trials.Materi yang disajikan dalam matakuliah Biologi Sel salah satunya adalah Penuaan Sel (Aging). Pada materi ini dapat dikembangkan penelitian In Silico untuk memperluas pengetahuan mahasiswa dengan inovasi pembelajaran berbasis pendekatan Bioinformatika dengan metode reverse screening. Metode penelitian yang digunakan adalah Model Pengembangan Dick and Carey (2009). Hasil penelitian berupa buku ajar matakuliah Biologi Sel berbasis In Silico yang telah divalidasi oleh ahli materi, media, dan uji coba skala kecil. Hasil dari ahli materi sebesar 91,43% untuk komponen kelayakan isi, 77,33% untuk kelayakan penyajian dan 72,72% untuk penggunaan bahasa. Untuk ahli media diperoleh 89,70% dan 93% untuk uji coba skala kecil.